2019
DOI: 10.1186/s12893-019-0536-2
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of intra orbital foreign body; diagnosis, management, and outcome: a case report

Abstract: Background An orbitocranial injury with a penetrating Intraorbital Foreign Body (IOFB) is listed as a rare cause of penetrating trauma. Since this type of trauma is considered a surgical emergency, taking a thorough history along with careful examination to find out the mechanism and cause of the trauma is crucial towards correct diagnosis and management of the disease. Case presentation A 35-year-old male patient was presented to the ER with an occupational craniofacia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
0
9
0
5
Order By: Relevance
“…This may be ascribed to hydration over a period of time. It has been observed that specific parameters like 4000 HU (Hounsfield unit) width/400 HU level are more effective for detection of IOrbWFB, and radiologists should be requested for these settings where retained wood is suspected [ 14 ]. If an object that is less dense than water is suspected, the parameters should be set to a level of -500 HU and a window width of 1500 HU to distinguish it from air [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be ascribed to hydration over a period of time. It has been observed that specific parameters like 4000 HU (Hounsfield unit) width/400 HU level are more effective for detection of IOrbWFB, and radiologists should be requested for these settings where retained wood is suspected [ 14 ]. If an object that is less dense than water is suspected, the parameters should be set to a level of -500 HU and a window width of 1500 HU to distinguish it from air [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the highly variable radiolucency of plastic. In some cases, plastic has been seen to resemble bone, while in others, it has mimicked air [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A tomografia computadorizada (TC) é considerada padrão ouro para a identificação de corpos estranhos penetrantes orbitais, visto que, devido à vantagem de uma resolução geométrica mais alta, surge a oportunidade de distinguir os tecidos calculando suas unidades de Hounsfield (HU), sendo um método barato e rápido, apesar disso, pode ser usada também a ressonância magnética (Chen et al, 2015;Cho et al, 2017;Bayramoglu et al, 2018;Singh et al, 2018;Mirzaei et al, 2019;Szabo et al, 2019). Entretanto, o diagnóstico e o gerenciamento são desafiadores, porque essas técnicas de imagem têm limitações e às vezes são inconclusivas, especialmente para corpos estranhos de madeira (Chen et al, 2015).…”
Section: Discussionunclassified
“…Uma das razões para esses desafios está relacionada ao grande número de variantes que contribuem para a aparência de corpos estranhos de madeira nas imagens, como tamanho e forma, tipo de madeira (macia ou dura), densidade física, estado de aeração, fresco, grau de absorção de água dos tecidos adjacentes e o tempo decorrido desde o início da lesão. A imagem formada por materiais de madeira é frequentemente confundida com gordura ou ar na TC, podendo contribuir para um diagnóstico confuso e equivocado (Jusué-Torres et al, 2016;Cho et al, 2017;Mirzaei et al, 2019;Szabo et al, 2019). Logo, detectar corpo estranho de madeira na imagem é difícil (Jusué-Torres et al, 2016), porque ela possui baixa densidade de Hounsfield deixando mais complicado distinguir do ar, simulando pneumocefalia e pneumo-orbita (Cho et al, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation